Legal review of the regulation of street vendors by the serang district police unit regarding the maintenance of public order, public order and public protection - Nanda Kurnia Perdiansyah; Asnawi Asnawi; Faturohman Faturohman (Institute Of computer Science (IOCS), 2024)
The purpose of this study is to assess the compliance of enforcement actions with Serang Regency Regulation Number 2 of 2018 concerning the Implementation of Public Order, Security, and Community Protection, and to identify various factors that cause violations or non-compliance by traders with this policy. The method used in this study is a normative juridical approach supported by empirical data. Data collection techniques were carried out through literature studies and direct interviews with traders, Satpol PP officers, and related parties within the Serang Regency Government. The data obtained were then analyzed qualitatively by interpreting legal provisions and relating them to social conditions in the field. The results of the study indicate that although enforcement actions by Satpol PP have a strong legal basis, their implementation in the field still encounters obstacles. Many street vendors refuse relocation due to economic reasons, the lack of adequate socialization, and the relocation location being considered non-strategic. This indicates a mismatch between legal policies and community needs. The conclusion of this study is that the success of enforcement is determined not only by legality, but also by the approach used in its implementation. Therefore, local governments are advised to implement fair, participatory, and social protection-based strategies so that enforcement policies can be accepted and implemented effectively in society.